Helminth biocoenosis of Lepus europaeus meridiei (Hilzheimer, 1906) from Pianosa island, Italy. (December 2022) - Guarniero, Ilaria; Bellinello, Enrica; Trocchi, Valter; Giannini, Francesca; Sulliotti, Valerio; Stancampiano, Laura
Abstract: Pianosa is a 10 km 2 Italian island in the Tyrrhenian Sea which is part of the Tuscan Archipelago National Park. In this island lives a brown hare population which, according to the literature, belongs to the ancestral taxon Lepus europaeus meridei that offers a unique opportunity to observe how the parasite biocoenosis shapes in condition of isolation, limited space availability and high population density. The aim of this work is to describe the helminth component community of a non-managed, isolated, and dense hare population, evaluating host-parasite relationship and parasite community structure. All 26 analyzed hares (13 males and 13 females) were in good physical conditions, and all of them harboured exclusively the nematode Protostrongylus oryctolagi only. This is the first report of this lungworm species in Italy. The estimated overall abundance was 48.15 worms per examined hare (range 3–258, median 50) and the parasites were unevenly distributed across host population, with few hosts having most parasites (aggregated or overdispersed distribution). No significant relationship was detected between the number of isolated parasites and hare sex and weigh. The effect of the isolation of Pianosa's hare population seems to have acted reducing parasite richness, while the high host density is probably the cause of the high prevalence and abundance of the single helminth species collected. In conclusion, despite the low impact of parasites confirmed also by the overdispersed parasite distribution, the low diversity of the studied parasite community sounds a warning for the management of the hare population and the whole Pianosa's ecosystem. Graphical abstract: Image 1 Highlights: Pianosa island is part of the Tuscan Archipelago National Park. Its population of Lepus europaeus meridei offers a unique opportunity to be studied. The parasite community is strongly dominated by Protostrongylus oryctolagi . It is the first report of this parasite in Italy. The low diversity of helminth community sounds a warning for the ecosystem health.